Efficacy and safety of Lianhua Qingwen granule in the treatment of non-influenza viral pneumonia: a randomized, double-blind, placebo-controlled, multicenter clinical study - Ma, Chengjie; Chen, Bojun; Li, Yanming; Gu, Li; Dong, Jianping; Xu, Zhenyang; Wei, Lijuan; He, Zhihong; Nie, Xiuhong; Feng, Shuwen; Cao, Bin; Sun, Lei; et al. (Frontiers in Medicine, 2024)
Abstract: Objective: To observe the effectiveness and safety of Lianhua Qingwen granule in the treatment of non-influenza viral pneumonia. Methods: This study was a multicenter, randomized, double-blind, placebo-controlled trial. Subjects who met the inclusion and exclusion criteria and were clinically diagnosed with viral pneumonia (negative for influenza virus) were randomly divided into the Lianhua Qingwen granule trial group and placebo control group. Patients in the trial group was given Lianhua Qingwen granule, 2 bags at a time, 3 times a day, and the controls were given placebo, with a treatment course of 7 days. Patients’ clinical symptoms and signs, and treatment-associated adverse events were observed. Subjects should be included in the full analysis set (FAS) as long as they were all given the medication and had an effectiveness test performed after randomization.Results: A total of 169 subjects were enrolled in 12 subcenters, including 151 (76 in the trial group and 75 in the control group) in the FAS and 140 (68 in the trial group and 72 in the control group) in the PPS. After 7 days of treatment, the clinical symptom relief rates were 82.98% (FAS) and 87.12% (PPS) in the trial group, and 75.11% (FAS) and 76.02% (PPS) in the control group, respectively. The clinical symptom relief rates in the trial group were significantly higher than those in the control group (p<0.001). Significant improvements in single symptoms of cough and expectoration in the trial group were observed compared with the control group (p<0.05). There were no statistical differences in fever, sputum color change, chest pain, muscle pain, dyspnea, chills, and thirst between the two groups (p＞0.05). Safety: There were no significant differences in body weight, vital signs, blood routine, urine routine, stool routine, and blood biochemical indicators (CK, AST, ALT,Cr,Bun) between the two groups before and after treatment (p＞0.05). During treatment, there were no significant differences in the incidence of adverse events and serious adverse events between the two groups (p＞0.05). Conclusion: Lianhua Qingwen granules improved the clinical symptoms of patients with non-influenza virus pneumonia, especially ameliorating cough and expectoration. Lianhua Qingwen granules were associated with good safety.